THE ROLE OF WORKING CAPITAL TO INCREASE SMALL BUSINESS ENTERPRISES - Nurul Fatmawati; Siti Hajar Nurlaila; Agus Sukoco; Reswanda T. Ade; Wahyu Mulyo Utomo (AIBPM Publisher, 2018)
The purposeThe objective of the research is to find the role of working capital that is sourced from own capital and credit capital in order to increase the value and capacity of small business sector MethodeThe research was conducted by conducting surveys, interviews, and documentation of Financial Statement recording. The data used in this study is the primary data. Based on the analysis, the Analysis of the People's Business Credit Process. The loan application stage, the review stage and credit analysis, the credit approval stage, the credit agreement stage and the credit disbursement stage. Result,The results found that the progress of SMEs is determined by the availability of working capital divided on their own capital and loan credit capital. Own capital and capital kedit provide a positive and significant impact on business volume on SMEs inSurabaya. The findings,arethe increase of business volume is based on the availability of working capital of the company. Working capital becomes important because in small scale industries the focus of business is on the production of production goods where the purchase of raw materials is in cash and not possible on credit. Keywords: capital,enterprises, business, credit